Opioid dispensing prior to opioid toxicity hospitalizations and emergency department visits in Canada, 2018–2022 - Bisola Hamzat; Grace Cheung; Dean T. Eurich; Jean-Luc Kaboré; Louis de Léséleuc; Zhaoyu Liu; Daniel McCormack; Houssem Missaoui; Jason R. Randall; Dana Shearer; David Stock; Tara Gomes (PLoS ONE, 2026)
Background Both pharmaceutical and non-pharmaceutical opioids contribute to overdoses and other drug-related harms in Canada; however, the role of these sources of opioids have been dynamic over the past two decades and vary geographically. Therefore, we sought to examine trends in the prevalence of prescription opioid exposure at the time of opioid toxicity hospitalizations and emergency department (ED) visits across Canada over the past 5 years. Methods We conducted a population-based repeated cross-sectional study of yearly opioid toxicities treated in an inpatient hospital setting in 6 Canadian provinces―British Columbia, Alberta, Saskatchewan, Manitoba, Ontario, and Quebec―between January 2018 and December 2022. We linked hospitalization records with community pharmacy dispensing data to determine active exposure to prescribed opioids at the time of opioid toxicity, annually and stratified by patient characteristics and type of opioid dispensed. In a secondary analysis, we replicated these methods among opioid toxicities treated in EDs in 5 provinces where data were available. Results We identified 23,876 opioid toxicity hospital admissions over the study period. Active opioid exposure at the time of hospital admission declined across provinces over time, apart from British Columbia (range, 20.0% in British Columbia to 47.5% in Quebec in 2018; 19.7% in British Columbia to 36.5% in Quebec in 2022). Generally, people ≥65 and females were proportionally more likely to have an active opioid exposure. When stratified by opioid type, we observed a shift towards active exposure to opioid agonist treatment (OAT), while active exposure to opioids for pain declined over time. Active opioid exposure was less common at the time of opioid toxicity ED visit but was more stable over time (range, 11.0% in British Columbia to 28.5% in Quebec in 2018; 14.9% in Alberta to 26.0% in Quebec in 2022), with only small declines in most provinces (Alberta, Ontario, and Quebec), and an increase in British Columbia (from 11.0% in 2018 to 16.8% in 2022), which was driven by a large increase in active OAT exposure. Conclusions Our findings highlight the increasing role of the potent unregulated drug supply in opioid toxicities across Canada, as well as important differences in the role of prescription opioids in harms across demographic groups, geography, and opioid indication.